TI_GERICHTE 14.2012.104 vom 29. August 2012 , Mancanza del titolo di rigetto provvisorio. Cessione. Legge sul contratto di assicurazione - TI Tribunale d'appello (2012)
Mancanza del titolo di rigetto provvisorio. Cessione. Legge sul contratto di assicurazione